Digitalization of the Sharia Economy: A Literature Review on the Role of Information Technology in Driving Economic Growth - Elvitrianim Purba (Journal of Economics, Management and Accounting (JEMA), 2025)
The digitalization of the sharia economy has become an important driver in strengthening the halal industry, Islamic banking, and sharia-based financial services globally. Information technology plays a strategic role in improving efficiency, expanding access, and fostering innovation within sharia-compliant economic activities. This study employs a literature review method to analyze the contribution of information technology to the growth of the sharia economy, particularly in the context of fintech, e-commerce, digital payment systems, and blockchain-based contracts. Findings from the reviewed literature indicate that the integration of technology into the sharia economy enhances financial inclusion, promotes transparency, and increases transaction security. Nevertheless, digital transformation also poses challenges such as regulatory adaptation, cybersecurity risks, and the need for digital literacy. This study contributes to the body of knowledge by offering an up-to-date synthesis of the role of information technology in driving the growth of the sharia economy, while highlighting opportunities and challenges in its implementation.